Early fungicide treatment reduces blackleg on canola but yield benefit is realized only on susceptible cultivars under high disease pressure. Issue 3 (4th May 2021) - Peng, Gary; Liu, Chang; Fernando, Dilantha W.G.; Lang, Ralph; Mclaren, Debra L.; Johnson, Eric N.; Kutcher, H. Randy; Singh, Gursahib; Turkington, T. Kelly; Yu, Fengqun
Abstract: Blackleg [ Leptosphaeria maculans (Desm.) Ces. & de Not.] is the most widespread disease of canola ( Brassica napus L.) on the Canadian prairies. It has a noticeably increased incidence in recent years possibly due to shifts in the pathogen population and erosion in cultivar resistance. This study was conducted to assess foliar-applied fungicides for mitigating the risk of blackleg. Field trials were conducted at five locations in the Black or Dark-Brown Soil Zones for four years using the susceptible canola 'Westar'. The fungicides pyraclostrobin (Headline ® ), azoxystrobin (Quadris ® ), propiconazole (Tilt ® ), and azoxystrobin + propiconazole (Quilt ® ) were applied at the 2–4 leaf stage against early infection. For comparisons, pyraclostrobin was also applied at bolting of 'Westar' and at the 2–4 leaf stage of two resistant cultivars ('43E01', '45H29'). These early treatments, except propiconazole, significantly reduced the mean disease incidence (MDI) and disease severity index (DSI) on 'Westar', relative to untreated control, reducing the impact of disease on yield by 16.5–26.9%. Late application of pyraclostrobin at bolting was ineffective. Two-application treatments, with pyraclostrobin at the 2–4 leaf stage and propiconazole at the bolting stage, or vice versa, provided no further efficacy or yield benefit relative to the early application of pyraclostrobin alone. None of the treatments showed substantial disease reduction or yield benefit in two low-disease station years (MDI <30%). On the resistant cultivars, pyraclostrobin reduced MDI and DSI, but showed no yield benefit. As resistant canola cultivars are used commonly on the prairies, a routine application of foliar fungicide is not recommended.